MANAJEMEN RISIKO PRODUKSI MELON HIDROPONIK DI LADANG PRAYOGA KECAMATAN PACIRAN KABUPATEN LAMONGAN - agung (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2022)
This study aims to determine the risk of hydroponic melon production in Prayoga Farm by using the FMEA (Failure Mode And Effect Analysis) method, Prayoga Farm focuses on melon production using a hydroponic system in a greenhouse. Hydroponic technology is a good alternative to obtain better production results in terms of quality, quantity, and continuity. In the production process of Prayoga Field, there must have been maximum production failure or less production, therefore the author would like to discuss about production risk management in Prayoga Field. In this study using a qualitative descriptive method using FMEA. Based on research that has been carried out related to the melon production process, it is concluded that in the praying field in all activities of the production process starting from the planning process of planting, care, and post-harvest there are 17 activities, and each activity has its own risks. After analyzing using the FMEA method, all activities from the production process are known to have a very low average risk level. With this, it is stated that the level of risk of hydroponic melon production in the prayoga field is very low or can be said to be not so severe. Suggestions that can be made for the production process at the Prayoga Field, namely from every activity starting from the planting planning process, the treatment process and also post-harvest, activities must be carried out with discipline and always check every activity so that everything can be controlled properly and the production process runs smoothly